Provisional study schedule of MUSIBOT. - Pierre Angelvy (22683450) (2025)
Introduction Botulinum toxin injections are a common treatment for managing spasticity resulting from central nervous system damage, including stroke, multiple sclerosis, and traumatic brain injury. However, the injections are associated with perceived pain, and many patients experience significant anticipatory stress regarding future sessions. The intensity of this stress varies among individuals. Music therapy, particularly receptive musical interventions structured around a U-shaped sequence, promotes progressive relaxation through distinct musical phases. This method has demonstrated efficacy in reducing pain and anxiety across various clinical contexts, including chronic and acute pain, Alzheimer’s disease, fibromyalgia, and neurologically mediated pain. Given the painful nature of botulinum toxin injections, this study proposes the use of receptive music therapy to improve patient tolerance of the procedure. We hypothesize that receptive musical intervention can reduce injection-induced stress in adults undergoing botulinum toxin treatment. To our knowledge, no studies have specifically investigated the effect of music therapy on stress related to botulinum toxin injections. We aim to conduct a prospective randomized (1:1) controlled trial to evaluate the impact of receptive music intervention on stress levels, measured via heart rate variability (HRV), during botulinum toxin injection sessions. The primary objective is to assess the effect of receptive musical intervention during botulinum toxin injections on injection-induced stress, measured by HRV. Secondary objectives include evaluating the intervention’s effects on pain intensity and anxiety levels. Methods and analysis Patient satisfaction following the music-assisted injection session will also be assessed. Additionally, the physician’s evaluation of the procedure and the patient’s perception of time during the session will be recorded. Ethics and dissemination All participants will provide written informed consent prior to enrollment. The study has received approval from the relevant institutional ethics committee (Comité de Protection des Personnes – ID: 25.00156.000468, Sud-Méditerranée IV, approved on 3 April 2025). Findings will be disseminated through peer-reviewed publications and presentations at scientific conferences. Trial registration ClinicalTrials.gov NCT06920524